Compressive stress strain behavior of crumb rubber concrete (CRC) and application in reinforced CRC slab. (30th March 2018) - Li, Danda; Zhuge, Yan; Gravina, Rebecca; Mills, Julie E.
Highlights: Crumb rubber from recycled tyre is used for replacement of fine aggregate in concrete. Peak stress, strain at peak stress, modulus of elasticity and energy dissipation ability are examined. Constitutive model for CRC is examined. Flexural behavior of reinforced CRC slab is examined both experimentally and numerically. Abstract: This paper presents the stress-strain behavior of CRC with rubber replacement percentages of 6%, 12% and 18%. The peak stress, strain at peak stress, modulus of elasticity, energy dissipation ability and the constitutive model under uniaxial compression were examined. Constitutive models for traditional concrete (TC) were applied to both TC and CRC. Comparisons between experimental results and the models were made. A constitutive model for unconfined CRC was then developed. A numerical study on the flexural behavior of reinforced CRC slabs was conducted with the application of the stress-strain model developed in the paper and the results agreed well with experimental tests.